IMPLEMENTING POSITIVE DISCIPLINE TO ENHANCE INDEPENDENCE AND RESPONSIBILITY AT TK ‘AISYIYAH BUSTANUL ATHFAL 1 KOTA MADIUN - Andriana; Malawi, Ibadullah; Sudarmiani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the issue of low independence and responsibility observed among Group B1 students at TK ‘Aisyiyah Bustanul Athfal 1 Kota Madiun. Initial observations indicated that most children relied heavily on teacher assistance for daily activities and lacked awareness regarding their tasks. This study aims to enhance these character traits by implementing the Positive Discipline approach, a method that emphasizes understanding and self-awareness without resorting to punishment. The study employed Collaborative Classroom Action Research based on the Kemmis and McTaggart model, conducted over two cycles. The subjects involved were 17 students from Group B1. Data collection techniques included observation, questionnaires, and documentation, which were then analyzed using the Miles and Huberman interactive model. The results demonstrated a significant improvement in each cycle. In the pre-cycle condition, the average level of independence and responsibility was only 25.46%. After implementing Positive Discipline through class agreements in Cycle I, these figures rose to 53% for independence and 54.8% for responsibility. By Cycle II, the scores surged to 88.23% for both traits, successfully exceeding the established success indicators. It can be concluded that the application of Positive Discipline is effective in building independence and responsibility in early childhood, while simultaneously creating a more enjoyable and meaningful learning Atmosphere.